The ASEAN economic community and beyond myths and realities - Basu Das, Sanchita (ISEAS Yusof Ishak Institute, 2016)
To aid in understanding the beginnings, development, and potential of these grand plans, this collection of 22 essays offers a rich analysis of ASEAN's own economic integration and other related initiatives.